Delirious Mania in a Case with Multiple Demyelinating Foci - Debdutta Nayak; Kamal Nath (Indian Journal of Private Psychiatry)
Introduction: A serious but underdiagnosed neuropsychiatric illness called delirious mania is described by the sudden onset of delirium, mania, and psychosis. Demyelination is the term used to describe the loss of myelin while axons are largely preserved. Depending on the site of insult, various neuropsychiatric manifestations may appear. We are discussing a case that was presented initially as mania but after a proper evaluation it was found to be a case of delirious mania along with multiple demyelinating foci in brain imaging, which had an impact on the presentation of this case. Case description: This is a case of 19-year-old man presented with complaints of talkativeness, tall claims, increasingly bizarre, and disorganized behavior with intermittent restlessness for the last 2 months. After a few trials with psychotropics, the patient started showing improvement with a combination of mood stabilizers and antipsychotics. Conclusion: Recent reports suggest that delirious mania may constitute up to 15% of all acute mania cases. When delirious mania is unrecognized or improperly treated, it can progress rapidly in severity and can become life-threatening. Like in our case, patients presenting with manic symptoms should also be properly evaluated for other underlying pathology which may have a significant impact on patient’s well-being.